2017
DOI: 10.1097/ta.0000000000001445
|View full text |Cite
|
Sign up to set email alerts
|

Early tranexamic acid administration ameliorates the endotheliopathy of trauma and shock in an in vitro model

Abstract: Antifibrinolytic and other protective effects of TXA administration on endothelial injury are time-dependent. This study supports the concept that the clinical efficacy of TXA administration requires "early administration."

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 40 publications
4
49
1
Order By: Relevance
“…CRASH-3 trial showed that the mortality benefits after adjustment were most pronounced when TXA was given < 3 h in mild-moderate Glasgow Coma Scale (GCS) score, however, mortality seemed to be the same in severe GCS score [13]. Which is in accordance with the abovementioned study that the early administration is better [18]. In a small RCT by Yutthakasemsunt et al, no mortality benefit was demonstrated in a mean time from injury of 7.1 h [11].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…CRASH-3 trial showed that the mortality benefits after adjustment were most pronounced when TXA was given < 3 h in mild-moderate Glasgow Coma Scale (GCS) score, however, mortality seemed to be the same in severe GCS score [13]. Which is in accordance with the abovementioned study that the early administration is better [18]. In a small RCT by Yutthakasemsunt et al, no mortality benefit was demonstrated in a mean time from injury of 7.1 h [11].…”
Section: Discussionsupporting
confidence: 80%
“…It prevent plasmin activation, reduces fibrinolysis, and stabilizes clot, without enhancing new clot formation [17]. Early TXA administration < 60 min has been shown to attenuate endothelial apoptosis and necrosis [18]. TXA has been shown to modulate pulmonary inflammation in trauma-induced acute lung injury [19].…”
Section: Discussionmentioning
confidence: 99%
“…aprotinin) on the inflammatory response . A recent publication also reported reduced lung barrier permeability by TXA in a rat model of polytrauma , while TXA was also recently reported to reduce ‘endothelialopathy’ of trauma and shock in an in vitro model . Hence it is reasonable to suggest that the blockade of plasmin generation by TXA in coagulopathic trauma patients, or indeed in other conditions associated with severe bleeding, may also have unintended consequences on outcome ; such effects could even be beneficial and may have contributed to the beneficial effects reported with TXA administration in the CRASH‐2 trial.…”
Section: The Influence Of the Plasminogen Activating System On The Immentioning
confidence: 98%
“…Tranexamic acid has protective effects on the endothelium and shows beneficial modulation of inflammation and other responses following ischaemia and reperfusion. 1,6 However, at times, reduced inflammatory response might be deleterious. This perspective has been suggested by the Glue Grant investigations, 7 which used a dataset obtained from 22 US trauma centres and examined the genomics of injury in a 12-year trial.…”
Section: Tranexamic Acid: Is It About Time?mentioning
confidence: 99%
“…One RCT showed lower survival with early enhanced feeding after hypophosphataemia 2 and in some studies enhanced feeding compromised recovery, 3 but most often the dosing, timing, and route of nutrition did not seem to affect hard clinical endpoints. [4][5][6] Such negative Nutrition in the ICU: sometimes route does matter and WOMAN trials. 2,3 Patients with severe brain injury or multi-organ trauma are more likely to present with shutdown of fibrinolysis than with massive bleeding.…”
Section: Tranexamic Acid: Is It About Time?mentioning
confidence: 99%